Towards a fast detection of microbial resistance to antibiotics - Leonardo Venturelli; Anne-Céline Kohler; Sandor Kasas (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
The antimicrobial resistance is the ability of bacteria and fungi to proliferate even in presence of antibiotic or antimycotic drugs [1]. In the last twenty years we have been witnessing a colossal increase in the antimicrobial resistance mainly due to the abuse and misuse of these compounds [2]. Although nowadays the use of antibiotics and antimycotics is more strictly regulated, antimicrobial treatment sometimes starts before a complete identification of the infectious agent [3-5].